ANALISIS PENGARUH BELANJA MODAL, PENYERTAAN MODAL, DAN PERTUMBUHAN PENDUDUK TERHADAP PERTUMBUHAN EKONOMI - Galuh Kirana; Susilo (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
Economic development can be observed through the economic growth of a region. Capital expenditure, local government capital investment, and population growth can have different impacts on economic growth. This study aims to determine the influence of capital expenditure, local government capital investment, and population growth on economic growth. Secondary data on variables were obtained from BPS and DJPK from regencies/cities in the provinces of Banten, DI Yogyakarta, and Central Java for the period 2012-2021, using the multiple linear regression analysis method. The findings of the study align with Keynesian Theory, indicating that capital expenditure has a significant positive effect on economic growth. In contrast, local government capital investment shows a significant negative direction toward economic growth, which is inconsistent with Harrod-Domar Theory. Meanwhile, population growth has a significant positive effect on economic growth.